Clostridium difficile associated diarrhea - 'suspect, inspect, treat, and prevent' - Shivani Tyagi; Aroma Oberoi (Wolters Kluwer Medknow Publications, 2014)
Context: Clostridium difficile is a fastidious, gram-positive, spore-forming bacterium responsible for infectious diarrhea and pseudomembranous colitis associated with significant morbidity and mortality. Only toxigenic strains produce disease in humans. Pathogenicity is dependent on the presence of diarrhea-producing toxins, named toxin A (TcdA) and toxin B (TcdB). Risk factors include depletion of protective gut flora by antibiotics and diminished immune response to C. difficile due to age and medical co morbidities; and increased use of proton-pump inhibitors (PPI). Treatment includes the stoppage of inciting antibiotics if possible, to allow regeneration of the normal gut microflora, and starting an antibiotic with activity against C. difficile. A good clinical suspicion in patient with co morbidities developing diarrhea during hospital stay can help reduce the burden of this treatable morbid infection. Our aim of doing this study was to determine the prevalence of this infection in our tertiary care hospital, so as to monitor its burden in future. Aims: To determine the prevalence of this infection in our tertiary care hospital. Settings and Design: A retrospective study was conducted in the department of Microbiology in a tertiary care hospital in North India. Materials and Methods: A total of 195 stool samples received over a period of 2 years were included in the study. An enzyme immunoassay was performed for the qualitative determination of toxins A and B from Clostridium difficile in stool samples. Results: A total of 13 (6.67%) stool samples out of 195 samples processed were positive for the presence of Clostridium difficile toxins A/B. Conclusions: CDI has become a global public health challenge today. Various studies show a prevalence rate between 11% - 22%. Lower prevalence rate revealed from our study (6.7%), makes it imperative to maintain a strict surveillance in our patients to ensure opportune detection and treatment